Impact of Body Mass Index on Pain Severity in Lumbar Facet Arthropathy: An Observational Study - Bella Chalista; Yusak Mangara Tua Siahaan; Tasya Pradhana (Universitas Pelita Harapan, 2025)
Background: Lumbar facet arthropathy is a common cause of chronic low back pain (LBP), with increasing evidence suggesting a link between obesity and pain severity. However, the relationship between body mass index (BMI) and pain intensity in facet-mediated LBP remains underexplored. Methods: A cross-sectional study was conducted on 50 patients aged 40–70 with clinically diagnosed lumbar facet arthropathy at Siloam General Hospital Lippo Village between February and June 2022. BMI was calculated and categorised per the WHO Asia-Pacific criteria. Pain severity was measured using the Numerical Rating Scale (NRS). Associations between BMI and pain severity were analysed using Chi-square or Fisher’s exact tests. Results: Most patients were female (52%) and aged 51–60 years (42%). Obesity was prevalent (46%), and 54% of participants experienced severe pain. A significant association was found between higher BMI and pain severity (p = 0.004), with overweight or obese patients having 8.73 times higher odds (95% CI: 2.04–37.30) of reporting severe pain compared to those with normal or underweight BMI. Discussion: These findings suggest a strong relationship between elevated BMI and increased pain severity in lumbar facet arthropathy. Potential mechanisms include increased mechanical loading and systemic inflammation mediated by adipokines. Conclusion: Higher BMI is significantly associated with greater pain severity in patients with lumbar facet arthropathy.